Effect of Trachyspermum copticum (L.) Link Microinjection in Nucleus Reticularis Paragigantocellularis on Morphine's Withdrawal Syndrome Sings - N Gheibi; H Jaffari; SR Miri; E Abbsai; M Khalili; H Jahani; S Yadegari (Institue of Medicinal Plants, ACECR, 2007)
Backgpound: Drug addiction is destructive misfortune and one of the most important problems in the world. Using the medical plants in medicinal history has valuable information and experiments in this field. Objective: According to research Trachyspermum copticum L. T. Copticum is effective in reducing of morphine's withdrawal syndrome, so in this study we investigate the effects of T. Copticum microinjection on nucleus reticularis paragigantocellularis (PGi) on morphine's withdrawal syndrome sings (MWSS). Method: After preparing the T.C fruit from height of the mountain in Khuzestan, aqueous extract of different concentration (Diluted 10, 100, 1000 times) was prepared by suckcele display. 32 male rats (Sprague Dawley with average weigh 250 - 300 gr) were randomized divided to 4 groups which dependent by intraperitoneum (I.P) injection with morphine. After cannulating the PGI with using the set of steriotaxi, microinjection of different doses of T. Copticum in PGI was done and naloxan (5 mg/kg) was injected I.P to groups. Results: Withdrawal syndrome signs (diarrhea, rearing, ptosis, irritability, tremor, agitation) were observed in 4 groups. Data evaluation and analysis was done by t-test and Mann-Whitney. Results show that T.C was significantly effective in reduction of MNSS such as (rearing ptosis, irritability) compared with control group. Conclusion: T. Copticum is probably sensitive on specific receptors in PGI.